Impact of decolonization protocols and recurrence in pediatric MRSA skin and soft tissue infections - Papastefan, Steven T. (J Surg Res, 2019)
BACKGROUND: Methicillin-resistant staphylococcus aureus (MRSA) colonization is associated with the development of skin and soft tissue infection in children. While MRSA decolonization protocols are effective in eradicating MRSA colonization, they have not been shown to prevent recurrent MRSA infections. This study analyzed the prescription of decolonization protocols, rates of MRSA abscess recurrence, and factors associated with recurrence. MATERIALS AND METHODS: This study is a single institution retrospective review of patients ≤ 18 years of age diagnosed with MRSA culture-positive abscesses who underwent incision and drainage at a tertiary care children’s hospital. The prescription of a MRSA decolonization protocol was recorded. The primary outcome was MRSA abscess recurrence. RESULTS: Three hundred ninety-nine patients with MRSA culture-positive abscesses who underwent incision and drainage were identified. Patients with prior history of abscesses, prior MRSA infection groin/genital region abscesses, higher number of family members with a history of abscess/cellulitis or MRSA infection and incision and drainage by a pediatric surgeon were more likely to be prescribed decolonization. Decolonized patients did not have lower rates of recurrence. Recurrence was more likely to occur in patients with prior abscesses, prior MRSA infection, family history of abscesses, family history of MRSA infection, Hispanic ethnicity, and those with fever on admission. CONCLUSIONS: MRSA decolonization did not decrease the rate of recurrence of MRSA abscesses in our patient cohort. Patients at high risk for MRSA recurrence such as personal or family history of abscess or MRSA infection, Hispanic ethnicity, or fever on admission did not benefit from decolonization.